Mind Mapping Method To Reduce Anxiety Ahead Of The Exam In Sociology Subjects - Muhammad Haris Novianto; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2013)
Mind mapping methods facilitate the students to recognize the course material in the form of keywords, symbols, images and colored lines. The purpose of this study was to determine the effect of mind mapping method to students' anxiety towards sociology examination. This study used a quantitative experiment approach with nonrandomized pretest-posttest control group design. Variables in this study were a mind mapping method as an independent variable (X) and students' anxiety towards sociology examination as a dependent variable (Y). Cluster random sampling was used as the sampling technique which class-XD as experimental group and Class-XA as the control group. Uncorrelated data/independent sample t-test was used to analyze data which calculated with SPSS 16.0 for Windows, the result showed (t=3.278; ρ = 0.002; ρ<0.05), it means there are differences of students' anxiety toward sociology examination to students who use the mind mapping methods that do not use the mind mapping method.